Analiza podstawowych problemów współczesnego kształcenia i wychowania w Republice Czeskiej - Vališová , Alena (Studia Edukacyjne, 2019)
The study tries to analyze briefly the current questions of the contemporary school system in the Czech Republic. The ongoing transformation of our school system implied specification of the basic key problems, in the socio-economical, philosophical, sociological, psychological, and pedagogical context. The respective problems are intentionally presented only with their brief characteristics, without taking a stand to them. Such a stand should be taken only after a qualified expert consideration of individual spheres of the problems mentioned.